Razširjenost kajenja med medicinskimi sestrami in zdravstvenimi tehniki v Pomurju ter njihova vloga v boju proti kajenju - Šuklar, Suzana (Obzornik zdravstvene nege, 2000)
The article states that more than a third of all nurses and nursing technicians in Pomurje region smoke, inspite of the fact that health workers should be role models for others.
Keywords: Health education; kajenje; medicinske sestre; Nurses; Pomurje; Smoking; Smoking cessation; Tobacco use disorder; zdravstvena vzgoja